(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
The association between serum 25-Hydroxy vitamin D (25-OH vitamin D) levels in hypothyroid subjects with and without thyroid peroxidase (TPO) antibodies is controversial. There is increasing evidence that 25-OH vitamin D level is associated with autoimmune diseases. The analytical cross-sectional case-control and hospital-based study were conducted at Professor Al-Mahdi M. Ali Center for Diabetes and Endocrinology in Khartoum from February to October 2020. Sixty subjects with hypothyroidism were recruited from the follow-up clinic. Thirty age and sex-matched subjects were used as control. Thyroid Function Tests [Thyroid-stimulating hormone (TSH), Free Thyroxine (FT4), and Free triiodothyronine (FT3)] were measured using TOSOH AIA 360system analyzer, and serum 25-OH vitamin D level was measured using semiautomatic I-Chroma-II reader and thyroid peroxidase antibodies (TPO antibodies) were measured in both cases and controls was estimated using ELISA. The results were analyzed using SPSS version 21. TSH was significantly increased in both TPO antibodies positive and TPO antibodies negative hypothyroid subjects than in the controls (22.3±4.44), (10.5±2.55) (3.42±0.75) with a P-value of 0.000. FT4 has decreased in both TPO antibodies positive and TPO antibodies negative subjects than in the control (0.51±0.21) (0.56±0.19) (2.0±0.55) with a P-value of 0.002. FT3 has significantly decreased in both TPO antibodies positive and TPO antibodies negative subjects than in the control (0.73±0.31)(0.73±0.49)(3.67±0.81) with a p-value of 0.0001. 25-OH Vitamin D level was lower among hypothyroid subjects than in the control. Subjects with positive TPO antibodies had lower 25-OH vitamin D levels than the TPO-antibody negative subjects compared to control (7.45±4.50̽) (10.5±7.18)(48.8±10.0) with P-value 0.000. Females 46(77%) were more than males 14(23%) and geographically most subjects were coming from the central part of Khartoum state.